Reviving the Nuanced Concept of Mother Earth in an Era of Non-Sustainability: A Serresian Reading of Marcel Pagnol’s L’eau des collines (ENTHYMEMA, 2018)
This essay examines the efforts of the writer Marcel Pagnol and the philosopher Michel Serres to revive the nuanced Amerindian metaphor of “Mother Earth” in the Anthropocene epoch.  Given that faulty anthropocentric logic and the unfounded doctrine of human exceptionalism concretize the nexus of the current era of non-sustainability, Pagnol and Serres attempt to breathe life back into this often misunderstood, multifaceted concept in an effort to (re-)envision a healthier relationship with the cosmic whole that sustains the existence of all sentient and non-sentient beings.  As this study highlights, this rich Amerindian metaphor opens up into philosophical, spiritual, and scientific dimensions.  Moreover, this investigation of the common threads that exist between Pagnol’s prose and Serres’s interdisciplinary, unconventional philosophy reveals the deep symbolism of the Amerindian metaphor of “Mother Earth.  This ecocentric concept could represent an invaluable point of departure for articulating the radical paradigm shift in our homocentric thinking that is paramount in order to avert the impending, anthropogenic ecological crisis that threatens to destroy all abundant life on this planet.  Pagnol’s prose and Serres’s philosophy promote a different way of being in the world in a human-centered universe that is increasingly defined by an environmental calamity of epic proportions.
Keywords: Marcel Pagnol; Michel Serres; metaphor of Mother Earth; biocentrism; cosmic spirituality